Prevention practices accounting fraud in managing village-owned business units and its approach using AI - Werastuti, Desak Nyoman Sri; Atmadja, Anantawikrama Tungga; Musmini, Lucy Sri; Adiputra, I Made Pradana; Sutoto, Agung; Hidayatulloh, A.Nururrochman; Sudarmanto, Eko; Purwanti, Purwanti; Sulistyowati, Nur Wahyuning (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
This study explores the practice of preventing accounting fraud in village-owned business units. The method used in this research is descriptive qualitative, and the approach is Artificial Intelligence (AI). For the descriptive qualitative methodology, the primary informants are several administrators of village-owned business units. The results of this study are two approaches, and the first is the conventional way, namely prevention carried out through work culture, opportunity removal, and financial report assessment; the 2nd approach is through technology or Artificial Intelligence applications. This research implies that work culture, elimination of opportunities, and evaluation of financial statements can prevent accounting fraud significantly if it is strengthened in written regulations. Bumdes managers need to make standard operating procedures in their activities. The AI approach results in Automated Data Analysis, Real-time Monitoring, Document Verification, and Automated Reporting System.